2007
DOI: 10.1158/1541-7786.mcr-06-0289
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-Rich 61 (CCN1) Enhances Chemotactic Migration, Transendothelial Cell Migration, and Intravasation by Concomitantly Up-Regulating Chemokine Receptor 1 and 2

Abstract: Cysteine-rich 61 (Cyr61; CCN1) plays an important role in tumor development and progression in many kinds of human malignancies. Here, we further show the enforced expression of the Cyr61 gene or treatment with recombinant Cyr61 protein enhanced expression of chemokine receptors CXCR1 and CXCR2 in gastric cancer AGS cells. Attenuation of Cyr61 levels in MKN-45 cells by transfecting with antisense Cyr61 significantly reduced the level of CXCR1 and CXCR2. It is suggested that Cyr61 tightly regulates the downstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 54 publications
1
41
0
Order By: Relevance
“…Cyr61-directed chondrosarcoma cells migration through avb3 integrin Cyr61 has been reported to stimulate directional migration and invasion of human cancer cells (25,26). We first examined whether Cyr61 express in human chondrosarcoma cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyr61-directed chondrosarcoma cells migration through avb3 integrin Cyr61 has been reported to stimulate directional migration and invasion of human cancer cells (25,26). We first examined whether Cyr61 express in human chondrosarcoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…The contrasting expression of Cyr61 in different types of cancer suggests that Cyr61 may exert a sophisticated function depending on cellular context. Previous studies have shown that Cyr61 modulates cell migration and invasion in human cancer cells (25,26). Cyr61-mediated migration may involve activation of integrin receptors (25).…”
Section: Introductionmentioning
confidence: 94%
“…95,96 The recent study indicates that Cyr61 could promote chemotactic migration, transendothelial cell migration and intravasation by concomitantly upregulating chemokine receptor 1 and 2(CXCR1/CXCR2) through integrin α v β 3 /Src/PI3K/Akt-dependent pathway. 97 In the MIF knockdown cells, Cyr61 expression has been significantly downregulated in both mRNA level and protein levels, which would lead to inhibition of Cyr61-dependent signaling pathway. It suggests Cyr61 is the important MIF-responsive gene which might contribute to MIF-mediated cell proliferation, proinflammation, angiogenesis and even tumorogenesis.…”
Section: Mif and C-myc Dependent Pathwaymentioning
confidence: 99%
“…Binding of Cyr61 to integrin a v b 3 in decidual natural killer cells is shown to induce the expression of vascular endothelial growth factor C, which is modulated by PI3-kinase and its downstream effector Akt . Additionally, Cyr61-expressing cells were reported to exhibit stronger potency in transendothelial migration and intravasation in human gastric adenocarcinoma cell lines through integrin a v b 3 /PI3-kinase/Akt-dependent pathway (Lin et al 2007). We have also found that downregulation of integrin-b 3 is induced by Cyr61 silencing.…”
Section: Discussionmentioning
confidence: 55%